Biochemical marker in familial amyloidotic polyneuropathy, Portuguese type. Family studies on the transthyretin (prealbumin)-methionine-30 variant. - Saraiva, M J (J Clin Invest, 1985)
A transthyretin variant with a methionine for valine substitution at position 30 [TTR(Met30)] is found in Portuguese patients with familial amyloidotic polyneuropathy (FAP). Effective, rapid, small- and semimicro-scale (immunoblotting) procedures were developed to determine whether or not TTR(Met30) is present in the plasma of an individual subject. The immunoblotting procedure employs only 0.10 ml of serum and can serve as a reliable procedure for the screening of large numbers of persons for the presence of TTR(Met30). In family studies of seven FAP kindreds, TTR(Met30) was found in 21 out of 41 asymptomatic FAP offspring, and its presence was not related to either age or sex. Thus, the mutant TTR segregated in accordance with the known autosomal dominant mode of inheritance of FAP. Total plasma TTR levels were not reduced in asymptomatic FAP offspring who were carriers of TTR(Met30), and no difference was observed between carriers and noncarriers of the mutant TTR. The ratios of the variant to normal TTR in plasma were estimated in asymptomatic FAP offspring and were similar to those found in FAP patients. In contrast, TTR(Met30) was relatively enriched in cerebrospinal fluid samples from two FAP patients. The significance of this finding is not known, but might relate to the preferential deposition of amyloid in the nervous system in FAP. A limited study was conducted involving simultaneous analysis of both stored (collected in 1975) and fresh serum from 20 FAP offspring, all of whom had been asymptomatic in 1975. In every subject, the results obtained with the stored and the fresh serum samples were in agreement. Six of these subjects developed clinical FAP since 1975; TTR(Met30) was present in each of these subjects. These several studies strongly suggest that the presence of TTR(Met30) in plasma constitutes a predictive biochemical marker of FAP in the preclinical phase of the disease. IMAGES: